Perspektif 'Ibn Arabi tentang Konsep Kebebasan dalam Tasawuf - Ah. Haris Fakhrudi (Department of Aqidah and Islamic Philosophy, Faculty of Ushuluddin and Philosophy, Sunan Ampel State Islamic University Surabaya, 2012)
This paper will discuss the meaning of freedom in the discourse of Sufi thought, especially of Ibn ‘Arabî. This is based on the consideration that Sufism before Ibn ‘Arabî’s more focused on ritualistic orientation for students and only revealed a variant of Sufi’s expressions, both on maqâmât and ahwâl. Therefore, the presence of Ibn ‘Arabî became the turning point in the discourse of Sufism by expressing his beliefs in the theoretical formulation. The doctrine of Sufism—which previously only implicitly contained in the words of the Sufi shaykh—in the hands of Ibn ‘Arabî flashed into an open, theoretical, and obvious and thus opened the door for anyone who has a high intelligence in reflecting at once and realizing the metaphysical theories through operational forms. Therefore, this article will discuss some of the key concepts in the thought of Ibn ‘Arabî including the meaning of freedom (al-hurrîyah) in Sufism, maqâm hurrîyah, and hâl hurrîyah obtained by the Sufis during their spiritual journey.